Novel RP-HPLC method development and validation for precise quantification of prochlorperazine maleate in pharmaceutical dosage forms - Shrisunder, Nikhil; Dhakad, Prashant Kumar; Gilhotra, Ritu (Journal of Applied Pharmaceutical Research, 2025)
Background: Prochlorperazine Maleate, a piperazine phenothiazine derivative, exhibits strong antiemetic and antipsychotic properties. However, existing analytical methods for its quantification in pharmaceutical formulations often face limitations regarding sensitivity, specificity, and accuracy. Many conventional techniques involve extensive sample preparation and prolonged analysis times, making them less feasible for high-throughput quality control. This study developed and validated a novel, precise, and highly sensitive reverse-phase high-performance liquid chromatography (RP-HPLC) method for Prochlorperazine Maleate quantification to overcome these challenges. Methodology: An RP-HPLC method was established using an Agilent Zorbax Bonus-RP column (250 × 4.6 mm, 5 µm) with a mobile phase of 0.1% formic acid and acetonitrile (70:30). The detection was performed at 258 nm using a diode array detector. Method validation followed ICH guidelines, assessing linearity, precision, accuracy, robustness, and sensitivity across a 100–150 µg/mL concentration range. Results and Discussion: The method displayed strong linearity (R² = 0.999). The LOD and LOQ were 1.76 µg/mL and 5.35 µg/mL, respectively. High precision (%RSD < 2%) and recovery rates (99–101%) confirmed accuracy. Robustness was established through consistent retention time and peak symmetry. Conclusion: This validated RP-HPLC method is reliable, sensitive, and cost-effective, making it ideal for routine pharmaceutical quality control and future stability studies.